Immunogenetic characteristics of hematopoietic stem cell donors representing the most numerous ethnic groups in Russia - E. V. Kuzmich; I. E. Pavlova; E. V. Belyaeva; L. N. Bubnova (Медицинская иммунология, 2024)
Development of criteria for the optimal donor selection based on the analysis of the allo-HSCT results, high-resolution HLA typing for the donor and recipient resulted in decreased incidence of immunological complications, primarily an acute «graft-versus-host reaction». However, due to the pronounced allelic polymorphism of the main histocompatibility complex (MHC) genes, the search for an optimal donor is ineffective in a number of patients. To increase the chances of selecting a donor for patients with rare HLA genotypes, the hematopoietic stem cell donor registries recruit the persons of various nationalities. An increased number of donors from different ethnic groups provide a broader immunogenetic diversity of the donor cohort. Currently, the registry of hematopoietic stem cell donors at the Russian Research Institute of Hematology and Transfusiology includes representatives of 49 nationalities, most of which, are considered themselves Russians. The third largest ethnic group in the registry comprises Tatars. The purpose of this study is a comparative analysis of immunogenetic characteristics of potential hematopoietic stem cells donors in the registry, who have self-identified as Russians and Tatars. As a result of the study, we have not found significant differences in frequencies of HLA allelic groups in the compared cohorts, a trend for higher frequency of the HLA-B*27 group was noted in Tatars. However, significant differences have been revealed for the distribution of HLA haplotypes in Russians and Tatars. The most common HLA haplotype among Tatars was A*02-B*44-DRB1*07, being much less common in Russians (4.61% vs 0.55%, p = 0.002). HLA haplotype A*03-B*13-DRB1*07, belonging to the ten most common among Tatars, was significantly less frequently detected in Russians (1.62% vs 0.08%, p = 0.026). HLA haplotype A*03-B*08-DRB1*03 was also significantly more common in Tatars compared to Russians (1.42% vs 0.06%, p = 0.026). HLA haplotypes A*02-B*18-DRB1*11, A*02-B*15-DRB1*04, A*02-B*15-DRB1*13, presented in Russians at a frequency of > 1%, were not determined among the tested Tatars. HLA haplotypes A*31-B*58-DRB1*04, A*24-B*44-DRB1*01, presented in Tatars at a frequency of > 1%, were not detectable in Russians. The results of our study indicate a need for recruiting more representatives of the Tatar ethnicity to the registry, thus increasing immunogenetic diversity of the donor pool and resulting into increased chances of compatible unrelated donor selection for the patients with HLA haplotypes, which are now underrepresented in our registry.